Indigenous rice: The construction of peasant identities base on cultural ecology - Weeranuch Yamyim; Chusak Wittayapak; Prasit Leepreecha; Charin Mangkhang (Penerbit Universiti Kebangsaan Malaysia, 2020)
This article studies how peasants have strategies or ways to construct identities through the cultivation of indigenous based on of community cultural ecology. This study used qualitative research methods as a guideline. Field surveys and data collection were conducted with emphasis on observation and group discussion. The result of the study is that peasants' identity is constructed through creating areas for indigenous rice which can be divided into 3 ways; 1) Construction of peasant identities through the ecology of Ban Nam Yen, that is, Ban Nam Yen’s indigenous rice is specific to the physical and ecological characteristics of the community as it is suitable for planting in highland areas, hillsides, highland-like crops, grows well in tropical climates, 2) Construction of peasant identities through creating a social space for indigenous rice by presenting indigenous rice to be known through social media, and creating community as agricultural tourism destinations, and 3) Construction of peasant identities through knowledge areas in the community, that is to say, making communities a source of learning both in the systematic learning using the community base for learning and informal learning as learning sources for those interested in field trips. For this reason, the construction of peasant identities is expressed by creating an area through indigenous rice as an instrument in the efforts to maintain the community’s identities.